Computer-Aided Design of α-L-Rhamnosidase to Increase the Synthesis Efficiency of Icariside I - Huang, Jia-Jun; Hu, Hao-Xuan; Lu, Yu-Jing; Bao, Ya-Dan; Zhou, Jin-Lin; Huang, Mingtao (Frontiers in Bioengineering and Biotechnology, 2022)
Icariside Ⅰ, glycosylation product of icaritin, is a novel effective anti-cancer agent with immunological anti-tumor activity. However, rare natural icariside I content hinders its direct extraction from plants. Therefore, we employed a computer-aided protein design strategy to improve the catalytic efficiency and substrate specificity of the α-L-rhamnosidase from Thermotoga petrophila DSM 13995, to provide a high-efficient preparation method. Several beneficial mutants were obtained by expanding the active cavity precisely. The catalytic efficiencies of all mutants ranged from 16 to 200-fold improvement over the wild-type TpeRha. The double-point mutant DH was the best mutant that showed the highest catalytic efficiency (kcat/KM: 193.52 s-1·M-1) against icariin, which was a 209.76-fold increase compared with the wild-type TpeRha. Besides, the single-point mutant H570A showed higher substrate specificity than that of the wild-type TpeRha in hydrolysis of different substrates. This study provides enzyme design strategies and principles for the hydrolysis of rhamnosyl natural products.